Pengembangan Buku Ajar Berbasis Literasi Sains dalam Meningkatkan Hasil Belajar IPA di Sekolah Dasar - Rizki Aria; Desy Crismas Silaban (Journal on Education, 2024)
This research aims to develop science textbooks based on scientific literacy to improve student learning outcomes. This research is a type of development research using a 4D model. The method used in analyzing data is quantitative descriptive expressed in the form of assessment scale categories. The validation results of the development book product stated that scientific literacy-based textbooks were suitable for use. Student learning outcomes after using the developed book products show differences so that it can be said that scientific literacy-based textbooks can improve student learning outcomes.